Correcting Deviations of the Lower Third of the Nose - Moubayed, Sami P.; Most, Sam P. (Facial Plastic Surgery, 2017)
By convention, a “deviated nose” is one in which the lower third is asymmetric with regard to the midline. The lower third of the nose is composed of the lower cartilages, as well as the dorsal and caudal nasal septum. Not only does the deviated nose cause a cosmetic deformity that is often disconcerting for patients, but it may also be associated with functional problems. Airway obstruction may result from a narrowed internal nasal valve in the middle third or from a deviated caudal septum in the lower third. The most common deviation involves both the middle and lower thirds and often requires addressing the underlying dorsal and caudal septum. The most effective technique to correct this type of deviation is the principle of extracorporeal septoplasty, either the traditional or modified, such as the anterior septal reconstruction (ASR) technique combined with the clocking suture. An isolated middle third deviation may be treated with a camouflage graft or a unilateral spreader graft. An isolated lower third deviation involving the septum should be treated with ASR. When an isolated lower third deviation only involves the lower cartilages, it may be corrected using suture techniques, cartilage division techniques, or grafting.
Keywords: rhinoplasty; deviation; deviated nose; septum